1989
DOI: 10.2134/agronj1989.00021962008100050004x
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield and Residual Soil Nitrate as Affected by Time and Rate of Nitrogen Application

Abstract: Efficient use of N fertilizer for corn (Zea mays L.) production is important for increasing economic return to the grower and for minimizing the potential impact on water quality. Time and rate of application are important management tools for improving N efficiency. This experiment was conducted for 3 yr on two nonirrigated southern Minnesota soils-a Mt. Carroll silt loam (fine-silty, mixed, mesic Mollie Hapludalf) and a Webster clay loam (fine-loamy, mixed, mesic Typic Haplaquoll)-to evaluate the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 13 publications
11
74
2
3
Order By: Relevance
“…2.5 to 4.1 kg N·ha -1 ·day -1 for the highest N fertilizer treatments. These rates were in accordance with values reported by Magdoff [18], Jokela and Randall [14] and Karlen et al [15], who found maximum uptake rates 2 to 3 weeks prior to silking. For the highest N fertilizer treatments, 64 to 81% of total N uptake was accumulated by silking.…”
Section: Soil No 3 -N Plant N Uptake and Grain Yieldsupporting
confidence: 92%
“…2.5 to 4.1 kg N·ha -1 ·day -1 for the highest N fertilizer treatments. These rates were in accordance with values reported by Magdoff [18], Jokela and Randall [14] and Karlen et al [15], who found maximum uptake rates 2 to 3 weeks prior to silking. For the highest N fertilizer treatments, 64 to 81% of total N uptake was accumulated by silking.…”
Section: Soil No 3 -N Plant N Uptake and Grain Yieldsupporting
confidence: 92%
“…However, in 2001, a delayed N application up to 130 kg ha -1 affected both growth parameters to a limited extent. Jokela and Randall (1989) reported an increase in yield when N rate was increased from 0 to 150 and 225 kg ha -1 , depending on the environment. Cerrato and Blackmer (1990) reported a linear increase in corn grain yield with N applications ranging from 0 to 100 kg ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Ces variations des diffe´rentes quantite´s de nitrates re´siduels ont pu eˆtre associe´es a`l'historique des champs, aux proprie´te´s chimiques et physiques du sol (Roth et Fox 1990), aux re´gimes hydriques du sol (Jokela et Randall 1989) et aux conditions climatiques. Par exemple, il est mentionne´que les saisons de ve´ge´tation se`ches ont tendance a`favoriser l'accumulation des nitrates dans le sol tandis que les saisons de croissance humides favorisent le lessivage des nitrates (Campbell et al 1983;Tran et Giroux 1998).…”
Section: Ré Sultats Et Discussionunclassified
“…Par exemple, il est mentionne´que les saisons de ve´ge´tation se`ches ont tendance a`favoriser l'accumulation des nitrates dans le sol tandis que les saisons de croissance humides favorisent le lessivage des nitrates (Campbell et al 1983;Tran et Giroux 1998). D'autre part, les saisons de croissance ayant des pe´riodes alterne´es se`ches et humides peuvent accroıˆtre la mine´ralisation de l'azote et favoriser l'accumulation des nitrates dans le sol a`la re´colte (Campbell et al 1983;Jokela et Randall 1989 (Be´langer et al 2003;Hong et al 2007). Des diffe´rences e´leve´es entre la dose applique´e et la dose optimale e´conomique d'azote ont indique´des risques accrus de lessivage par une accumulation excessive de la quantite´de nitrates dans le sol (Fig.…”
Section: Ré Sultats Et Discussionunclassified
See 1 more Smart Citation